1990
DOI: 10.1159/000261276
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Enamel Constituents in Streptococcus mutans Plaque during Intraoral Demineralization

Abstract: Studies were carried out with an intraoral demineralizing system in order to determine whethei calcium and inorganic phosphate (PI) accumulate in plaque during active demineralization of enamel. Blocks of bovine enamel were coated with Streptococcus mutans and were carried in palatal appliances worn by human volunteers. Demineralization was determined as changes in the iodide penetrability (delta Ip) of the enamel surfaces. Ca and PI were determined in the extracellular spaces of the synthetic plaque. Delta Ip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…All these studies have been carried out with plaque grown on an enamel substratum, so uptake of Ca from enamel into plaque may have been responsible for failure to find low Ca levels after sugar intake. In fact, Cury et al [1997] noted white spots on the enamel which were especially marked after the 8 times frequency application, supporting the suggestion of Kashket and Yaskell [1990] that enamel provides Ca to plaque under these conditions. Our study, where enamel cannot have affected the results, shows clearly that increasing frequency of sugar application causes the development of plaque having progressively less Ca, i.e.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…All these studies have been carried out with plaque grown on an enamel substratum, so uptake of Ca from enamel into plaque may have been responsible for failure to find low Ca levels after sugar intake. In fact, Cury et al [1997] noted white spots on the enamel which were especially marked after the 8 times frequency application, supporting the suggestion of Kashket and Yaskell [1990] that enamel provides Ca to plaque under these conditions. Our study, where enamel cannot have affected the results, shows clearly that increasing frequency of sugar application causes the development of plaque having progressively less Ca, i.e.…”
Section: Discussionsupporting
confidence: 55%
“…All whole-plaque studies to date that we are aware of have been carried out using natural plaque from enamel surfaces, or from enamel surfaces in in situ experiments [Cury et al, 1997] where mineral ion movements may be obscured by contributions from enamel [Kashket and Yaskell, 1990]. Furthermore, overnight starved plaque has been shown to be more susceptible to Ca loss than unstarved plaque [Ashley, 1975], 2-day-old plaque more susceptible than mature plaque [Ashley and Wilson, 1977a], and plaque on free smooth surfaces more susceptible than plaque on the less accessible approximal surfaces of teeth [Wilson and Ashley, 1990].…”
mentioning
confidence: 99%
“…The present observations did not support the assumption. Instead, the Ca and Pi derived from enamel during active demineralization [Kashket and Yaskell, 1990] appeared to play a significant role in regu lating further mineral dissolution.…”
Section: Regulation O F Demineralizationmentioning
confidence: 99%
“…With the CL-supplemented sweet cookies, for example, the calcium concentrations in the plaque space rose and then fell from 32.4±6.0mM at 1 min to 13.3±4.1 mM at 15 min ( fig. 2), the latter concentration being no different statisti cally from calcium concentrations in plaque under actively demineralizing conditions [Kashket and Yaskell, 1990]. Calculations using the measured plaque Ca and Pi concen trations [Moreno and Margolis, 1988] indicated that the plaque remained saturated with respect to enamel at 5 min (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…Presumably, cal cium, would be most effective in regulating demineraliza tion as the plaque pi 1 fell [Kashket and Yaskell, 1990]. Data arc shown in figure 2.…”
Section: Calcium Accumulationmentioning
confidence: 99%